“Jornalismo vale de lágrimas”: a hiperprodução semiótica da negatividade no telejornalismo da Globo - Pádua, Gesner Duarte (2022)
This research investigates the semiotic hyperproduction of news negativity in TV Globo's two main network news programs: Jornal Hoje and Jornal Nacional. It aims to verify, in a comparative way, how negative news values appear structurally in the programs and which images of the world are constructed in this model of telejournalism saturated by the negative. The empirical corpus is composed by 24 editions of each television news, referring to the month of January 2020. The methodology adopted is qualitative and quantitative and comprises the use of the Content Analysis technique for data collection and systematization. The theoretical instrument for interpreting and discussing the results is based on the theories of Journalism and Communication, mainly referring to newsworthiness studies, and on the Semiotics of Culture, in the strand developed by Ivan Bystrina and Norval Baitello Junior, focused on communicational processes. In line with the transdisciplinary proposal of this semiotic current, the study also uses contributions from Sociology, Anthropology and Experimental Psychology to discuss the characteristics of social negativity and negativity in the professional journalistic culture. The research points to the massive presence of negative news in both newscasts: 80% in Jornal Hoje and 79% in Jornal Nacional, with the prevalence of themes political crisis, crime, natural disasters, crisis in public services, diseases, and economic crisis. Positive news appears in a very disproportionate number: 12% in JH and 17% in JN, followed by undetermined: 8% and 4% respectively. The hegemonic frames constructed by these newscasts, dominated by the negative, suggest the image of a world in a permanent state of deterioration, disorder, imminent ruptures of normality, where the need to be on constant alert is imperative, and which takes audience to reminiscences of the human life in the dangerous and hostile desert environment of primitive societies. The research also discusses some causes and consequences of the phenomenon and initiatives to oppose this model of journalism, called “valley of tears”